MANAJEMEN PELAYANAN KESEHATAN DI PUSKESMAS BELANG KABUPATEN MINAHASA TENGGARA - Mokodaser, Margitha; Pangkey, Masje Silija; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: the problems that often arise in instances of Government clinicsespecially in this regard contained in management functions such as planning,organizing, implementing, and monitoring at regular intervals. Based on thepermasalahaan that occur in the context of Pererencanaan, organizing,implementing and monitoring. Aspects of management became a very importantthing to note. Departing from the importance of the required management withinthe Organization, so that the researcher is interested in lifting and discussingand researching the title research on the management of health services at theClinic, and forms the Southeast Minahasa Regency Striped Subdistrict. Thisstudy uses qualitative methods because it is done in a natural condition.Sugiyono (2013) suggested that the research methods qualitative researchmethods are used to examine the conditions of natural objects, whereresearchers are as a key instrument, techniques of data collection conducted inthe combined inductive in nature, data analysis, and the results of the qualitativeresearch emphasizes the significance of on generalities.The number ofinformants 11 people, consisting of 1 head of clinics, 1 poly head General, I headthe poly Poly 1 head gear, maternal and child health, seven patients.Keywords: Health Services Management